2019
DOI: 10.1111/gcb.14701
|View full text |Cite
|
Sign up to set email alerts
|

Response of cyanobacteria and phytoplankton abundance to warming, extreme rainfall events and nutrient enrichment

Abstract: Cyanobacterial blooms are an increasing threat to water quality and global water security caused by the nutrient enrichment of freshwaters. There is also a broad consensus that blooms are increasing with global warming, but the impacts of other concomitant environmental changes, such as an increase in extreme rainfall events, may affect this response. One of the potential effects of high rainfall events on phytoplankton communities is greater loss of biomass through hydraulic flushing. Here we used a shallow l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 86 publications
(151 reference statements)
2
73
1
3
Order By: Relevance
“…Taken together, these data suggest that ameliorated environments (such as CO2 enrichment, temperature increase in some parts of the world, or nutrient enrichment) may at least initially increase variation more than expected based on increases to system carrying capacity (extra energy input) alone (Biswas et al, 2017;Burson et al, 2018;Gudmundsdottir et al, 2011;Richardson et al, 2019;Stevenson et al, 2008).…”
Section: Environmental Quality Affects Phenotypic Variationmentioning
confidence: 80%
“…Taken together, these data suggest that ameliorated environments (such as CO2 enrichment, temperature increase in some parts of the world, or nutrient enrichment) may at least initially increase variation more than expected based on increases to system carrying capacity (extra energy input) alone (Biswas et al, 2017;Burson et al, 2018;Gudmundsdottir et al, 2011;Richardson et al, 2019;Stevenson et al, 2008).…”
Section: Environmental Quality Affects Phenotypic Variationmentioning
confidence: 80%
“…Taken together, these data suggest that ameliorated environments (such as CO 2 enrichment, temperature increase in some parts of the world, or nutrient enrichment) may at least initially increase variation more than expected based on increases to system carrying capacity (extra energy input) alone (Biswas et al., 2017; Burson et al., 2018; Gudmundsdottir et al., 2011; Richardson et al., 2019; Stevenson et al., 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Results of previous studies have shown that composition, biomass and diversity of phytoplankton is primarily determined by nutrients (Reynolds and Irish, 1997;Rangel et al, 2012). Results of other studies have shown that succession of phytoplankton communities is controlled by physical conditions such as light (Edwards et al, 2015), water temperature (Rasconi et al, 2017;Neukermans et al, 2018), mean depth (Pinckney et al, 2015), flushing rate (Cañavate et al, 2015) and their interactions (Hart et al, 2015;Edwards et al, 2016;Burson et al, 2018;Richardson et al, 2019). Competition for resources, predation, environmental change and rates of mutation and plasticity will affect succession of taxonomic and functional groupings, but whether there is seasonal congruence between functional and taxonomic groupings or not remains unclear in natural communities.…”
Section: Introductionmentioning
confidence: 99%